A Whole-Body Physiology Model to Investigate Respiratory Function During Exercise Across Different Age Cohorts - Austin Baird; Rachel A. Umoren; Steven A. White; Megan Gray; Taylor L. Sawyer (Journal of Respiration)
Background: There is a limitation in understanding complete cardiopulmonary function during moments of exhaustive exercise due to invasive measurement techniques. We asked how cardiopulmonary function is perturbed during times of exercise in different age cohorts: 6–11 and 11–18. We sought to broadly analyze how age and oxidative stress during exercise differ across age cohorts. Methods: We present a whole-body physiology model that connects the nervous, cardiovascular, respiratory, and oxygen transport and binding systems. We connect these models using a lumped parameter representation of the cardiovascular and respiratory systems. Results: we observe distinct age-related difference in physiological response to exercise. These responses consist of respiratory, cardiovascular, and nervous system perturbations that are distinct across these age groups.